Impact of the School Coexistence on Academic Performance according to Perception of Typically Developing and Special Educational Needs Students - Cerda, Gamal A. (2018)
This descriptive correlational study aims to compare the perception about eight dimensions of school coexistence of typically developing high school students (n = 545) and students with special educational needs (n = 75) from Chile and their relationship with the general academic performance.  Based on the analysis of hierarchical and non-hierarchical clusters, multiple regression and logistic regression, it was found that students with special educational needs have a less favorable perception in almost every dimension analyzed; especially, in those aspects related to school victimization, aggression, and indiscipline. Likewise, they perceive that they have a limited peer social network, as well as limited normative adjustment and a lower perception about their own positive interpersonal skills. The multiple regression and logistic regression models allow confirming that the dimensions of school coexistence account for between 20% and 27% of the academic performance variability. The aforementioned models highlight the role and negative effect of the level of victimization perceived by students, as well as the perception about the occurrence of indiscipline situations in the classroom, and the fact of belonging to the group of students with special educational needs, and to the group of male students. The findings are analyzed and discussed in light of the implications for high social vulnerability educational contexts.